Coated paper as well as preparation method and application thereof
By using raw materials such as tannin acid, ε-polylysine, cationic etherified starch and alkylkane dimer, the application restriction of paper packaging materials in high humidity environments and food packaging fields was solved, and biomass-based coating paper with excellent mechanical strength, hydrophobicity, oxidation resistance and antibacterial properties were prepared.
Patent Information
- Application Number
- CN202411789096.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Due to its disadvantages such as poor water stability, low mechanical strength and inability to microorganisms, paper packaging materials have limited their wide application in high humidity environments and food packaging fields.
A kind of antioxidant, antibacterial and hydrophobic applicator solution is prepared by raw materials such as tanninic acid, ε-polylysine, cationic etherified starch and alkylkone dimer, and applied it to the surface of the base paper by immersion to prepare biomass-based coating paper.
It improves the tensile index of coated paper, enhances its hydrophobicity, significantly improves antioxidant and barrier properties, and has excellent antibacterial effects on Staphylococcus aureus and E. coli.
Smart Images

Figure CN119615671A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of packaging material preparation, and in particular to coated paper and a preparation method and application thereof. Background Art
[0002] In recent years, the concept of green and circular development has gradually gained popularity. Plastic packaging materials have been gradually restricted by various countries due to the non-renewable and non-biodegradable characteristics of petroleum-based raw materials. Paper packaging materials have gradually attracted people's attention due to their advantages such as wide sources of raw materials, renewable, light weight, low cost, simple production process, green and safe. According to statistics, the consumption of paper packaging materials accounts for more than 40% of the total consumption of four traditional packaging materials: paper, plastic, glass and metal. However, due to the hydrophilic properties and porous structure of paper itself, its wet strength is low and its barrier properties are poor, making it difficult to be more widely used. In a high humidity environment, paper packaging products are also prone to breed bacteria, causing food to spoil and mold, which seriously limits the multifunctional utilization of paper products. Summary of the invention
[0003] Based on the above content, the present invention provides a coated paper and a preparation method and application thereof.
[0004] To achieve the above object, the present invention provides the following solutions:
[0005] One of the technical solutions of the present invention is a sizing solution, the raw materials of which include tannic acid, ε-polylysine, cationic etherified starch, alkyl ketene dimer and water;
[0006] The mass volume ratio of the tannic acid, ε-polylysine, cationic etherified starch, alkyl ketene dimer and water is (4-12) g: (0.2-1) g: (0.4-1.2) g: (0.6-1.5) g: 200 mL.
[0007] The second technical solution of the present invention is a method for preparing the sizing solution, comprising the following steps:
[0008] Dissolve tannic acid in 1 / 2 volume of water, then add ε-polylysine to obtain a tannic acid / ε-polylysine solution;
[0009] dissolving the cationic etherified starch in the remaining 1 / 2 volume of water to obtain a cationic etherified starch solution;
[0010] The tannic acid / ε-polylysine solution is mixed with the cationic etherified starch solution and then gelatinized to obtain a uniform solution;
[0011] Alkyl ketene dimer is added to the homogeneous solution to obtain the sizing solution.
[0012] The third technical solution of the present invention is the use of the sizing solution in the preparation of coated paper.
[0013] A fourth technical solution of the present invention is a coated paper, the raw materials of which include base paper and the sizing solution.
[0014] A fifth technical solution of the present invention is a method for preparing the coated paper, comprising the following steps: immersing the base paper in the sizing solution, and then pressing and drying to obtain the coated paper.
[0015] A sixth technical solution of the present invention is the use of the coated paper in the preparation of packaging materials.
[0016] The present invention discloses the following technical effects:
[0017] Paper-based materials are favored by people because of their advantages such as green environmental protection, good biocompatibility and low cost, but their further widespread application is limited by their disadvantages such as poor water stability, low mechanical strength and intolerant to microorganisms. The present invention uses cationic etherified starch (CS), alkyl ketene dimer (AKD), tannic acid (TA) and ε-polylysine (ε-PL) as raw materials to prepare an antioxidant and antibacterial hydrophobic sizing solution, and uses the sizing solution to prepare biomass-based coated paper. Compared with the base paper, the tensile index of the coated paper is increased by 45%, the water contact angle can reach more than 135°, the antioxidant property to DPPH reaches more than 90%, and the ultraviolet barrier performance is also greatly improved. In addition, the antibacterial effect of the coated paper on Escherichia coli and Staphylococcus aureus was evaluated by the antibacterial circle test method. The results show that the coated paper has excellent antibacterial effect on Staphylococcus aureus and Escherichia coli, and the antibacterial effect on Staphylococcus aureus is more significant. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 The figure is a schematic diagram of the preparation process of TC / PL coated paper of the present invention.
[0020] Figure 2 (a) is the optical photograph of uncoated (base paper) and TC / PL coated paper; (b) is the thickness and weight of uncoated and TC / PL coated paper; (c) is the FT-IR spectrum of uncoated and TC / PL coated paper.
[0021] Figure 3SEM images of (a) uncoated, (b) TC / PL-0.1%, (c) TC / PL-0.3%, and (d) TC / PL-0.5%.
[0022] Figure 4 Physical properties of uncoated and TC / PL coated paper: (a) tensile index; (b) breaking length; (c) whiteness; (d) UV transmittance.
[0023] Figure 5 (a) DPPH radical scavenging rate of uncoated and TC / PL coated paper; (b) changes in DPPH radical reaction.
[0024] Figure 6 (a) Hydrophobic mechanism of TC / PL coated paper; (b) water contact angle; (c) wetting by milk, juice, Coca-Cola, coffee and acid and alkali solutions.
[0025] Figure 7 The inhibition zones of uncoated and TC / PL coated paper (a) Escherichia coli; (b) Staphylococcus aureus; (c) inhibition zone diameter. DETAILED DESCRIPTION
[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0027] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0028] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0030] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0031] Bamboo is a fast-growing plant resource widely distributed in Asia. In recent years, it has gradually been identified as a substitute for wood. Fully utilizing the advantages of bamboo forest resources is an effective way to alleviate the current shortage of wood resources. Bamboo has a high cellulose content and a fiber length between coniferous wood and broadleaf wood. It has good pulping properties and is a high-quality raw material for pulping and papermaking.
[0032] At present, people use a variety of methods such as chemical modification, atomic layer deposition and physical blending of hydrophobic and antibacterial substances to enhance the water resistance and antibacterial properties of cellulose paper. In industrial production, sizing is a common method to improve paper performance, which is divided into surface sizing and internal sizing. The latest research on paper hydrophobicity focuses on surface sizing because it can effectively retain the dosage of hydrophobic compounds. Commonly used paper sheet hydrophobic sizing agents include ASA, AKD, and rosin size. By depositing non-reactive sizing agents such as starch, polyvinyl alcohol and chitosan on the surface of paper, the physical properties of paper including surface strength, wettability and barrier properties can be improved. Starch and its derivatives are the most used components in paper products except cellulose fibers and mineral fillers. Compared with other sizing agents, they have the advantages of low cost, good biocompatibility and high yield. They are the most widely used sizing agents in current industrial production. Among starch and its derivatives, the use of cationic starch has increased significantly in the past few years because it can not only be used as a paper dry strength agent to increase the bonding between fibers, but also its cationic groups can have a better retention effect on anionic fibers, thereby reducing wastewater load.
[0033] Tannic acid is a natural polyphenol compound with antioxidant, antibacterial, anti-inflammatory and hemostatic properties. It has been approved for clinical and food additive use, so it is safe and feasible to use in the field of food packaging. Natural ε-polylysine is a typical cationic antimicrobial peptide with broad-spectrum antibacterial activity against bacteria and fungi. It causes physiological damage to cells by adsorbing on the surface of microbial membranes. Therefore, based on the antioxidant and antibacterial functions of tannic acid and ε-polylysine, they can be used as antibacterial additives for food packaging paper to give paper antimicrobial properties.
[0034] The present invention uses cationic starch (CS) as a sizing matrix to enhance fiber strength, alkyl ketene dimer (AKD) as a hydrophobic agent, tannic acid (TA) as an antioxidant, and ε-polylysine (ε-PL) as an antibacterial agent to prepare a bio-based paper sizing solution. Bleached bamboo pulp is used as a fiber raw material to prepare bleached bamboo pulp paper, and a layer of antioxidant, antibacterial and hydrophobic starch-based coating is deposited on the surface of the bamboo pulp base paper by an impregnation method. The preparation flow chart is as follows: Figure 1 The morphology, hydrophobicity, anti-oxidation, mechanical strength, etc. of the modified bleached bamboo pulp paper were studied, and its antibacterial activity was evaluated. The method of the present invention is efficient, simple, green and environmentally friendly. The coated paper prepared by the method of the present invention has broad application prospects in the field of food packaging.
[0035] The first aspect of the present invention provides a sizing solution, the raw materials of which include tannic acid, ε-polylysine, cationic etherified starch, alkyl ketene dimer and water;
[0036] The mass volume ratio of the tannic acid, ε-polylysine, cationic etherified starch, alkyl ketene dimer and water is (4-12) g: (0.2-1) g: (0.4-1.2) g: (0.6-1.5) g: 200 mL.
[0037] In the present invention, if the amount of alkyl ketene dimer is too low, the sizing effect will not be achieved; if the amount of alkyl ketene dimer is too high, it will cause agglomeration and uneven dispersion in the sizing solution. Therefore, the present invention preferably limits the amount of alkyl ketene dimer to the above parameter ratio range.
[0038] In the present invention, if the amount of cationic etherified starch is too low, the paper strength will be low; if the amount is too high, the viscosity of the emulsion will be too high, the amount of paper sizing will increase, the paper will become brittle and the rigidity will increase. Therefore, the present invention preferably limits the amount of cationic etherified starch to the above parameter ratio range.
[0039] The second aspect of the present invention provides a method for preparing the sizing solution, comprising the following steps:
[0040] Dissolve tannic acid in 1 / 2 volume of water, then add ε-polylysine to obtain a tannic acid / ε-polylysine solution;
[0041] dissolving the cationic etherified starch in the remaining 1 / 2 volume of water to obtain a cationic etherified starch solution;
[0042] The tannic acid / ε-polylysine solution is mixed with the cationic etherified starch solution and then gelatinized to obtain a uniform solution;
[0043] Alkyl ketene dimer is added to the homogeneous solution to obtain the sizing solution.
[0044] In a preferred embodiment of the present invention, the pH of the cationic etherified starch solution is 4.
[0045] In some specific embodiments of the present invention, the pH of the cationic etherified starch solution is adjusted to 4 by adding an acetate buffer solution with a pH of 3.5.
[0046] In a preferred embodiment of the present invention, the gelatinization is specifically gelatinization at 95° C. and a rotation speed of 500 rpm for 30 minutes.
[0047] In a preferred embodiment of the present invention, the temperature for adding the alkyl ketene dimer to the homogeneous solution is 60°C.
[0048] The third aspect of the present invention provides a use of the sizing solution in preparing coated paper.
[0049] A fourth aspect of the present invention provides a coated paper, the raw materials of which include base paper and the sizing solution.
[0050] In some specific embodiments of the present invention, the base paper is bleached bamboo pulp base paper, which is prepared by the following steps: beating the bleached bamboo pulp to a beating degree of 70°SR to obtain wet pulp, dispersing the wet pulp with a pulp deflaker and then using a paper sheet former to make paper of the bleached bamboo pulp wet paper; pressing the bleached bamboo pulp wet paper and then drying it to obtain the bleached bamboo pulp base paper.
[0051] A fifth aspect of the present invention provides a method for preparing the coated paper, comprising the following steps: immersing the base paper in the sizing solution, and then pressing and drying to obtain the coated paper.
[0052] In a preferred embodiment of the present invention, the immersion temperature is 60° C. and the time is 10 s; the pressing pressure is 0.5 MPa and the time is 10 min; and the drying temperature is 105° C. and the time is 15 min.
[0053] A sixth aspect of the present invention provides use of the coated paper in preparing packaging materials.
[0054] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0055] The schematic diagram of the preparation process of TC / PL coated paper of the present invention is as follows Figure 1 As shown (in the figure, CS / ε-PL-AKD represents TC / PL sizing solution).
[0056] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0057] Example 1
[0058] 1. Materials and Methods
[0059] 1.1 Materials
[0060] Bleached bamboo pulp board (absolute dry pulp) was provided by Mudanjiang Hengfeng Paper Co., Ltd. (Heilongjiang). Food-grade tannic acid was purchased from Wufeng Chicheng Biotechnology Co., Ltd. (Hubei, China). Cationic etherified starch was purchased from Hefei BASF Biotechnology Co., Ltd. (Anhui), with a viscosity of 690-1200mpa.S (6% 95°C) and a degree of substitution of 0.025-0.03. ε-Polylysine (food grade) was purchased from Zhejiang Xinyinxiang Bioengineering Co., Ltd. (Zhejiang). AKD emulsion was purchased from Dongguan Huiteng New Materials Co., Ltd. (Guangdong), which is a cationic AKD emulsion with a solid content of 12.5% ± 0.5% and a pH value of 3-4. LB broth agar was purchased from Shenggong Bioengineering (Shanghai) Co., Ltd. LB broth was purchased from Beijing Aoboxing Biotechnology Co., Ltd.
[0061] 1.2 Preparation of TC / PL coated paper
[0062] 1.2.1 Preparation of bleached bamboo pulp base paper (referred to as base paper)
[0063] Weigh 360g of absolute dry pulp and use a Valley beater to beat the bleached bamboo pulp to a beating degree of 70°SR. Wet pulp equivalent to 1.256g of absolute dry pulp is measured and dispersed in a pulp decompressor and then papered using a sheet former with a weight of 37±1g / m 2 , a round bleached bamboo pulp wet paper sheet with a diameter of 20 cm. The round bleached bamboo pulp wet paper sheet was pressed at a pressure of 0.5 MPa for 10 minutes and then dried in a plate dryer at 105°C to obtain bleached bamboo pulp base paper, which was stored in a sealed bag.
[0064] 1.2.2 Preparation of TC / PL sizing solution
[0065] Weigh 8g of tannic acid (TA) and dissolve it in 100mL of deionized water, then dissolve ε-polylysine (0.2g, 0.6g, 1g) in the tannic acid solution to obtain a tannic acid / ε-polylysine solution. Weigh 0.8g of cationic etherified starch and dissolve it in 100mL of deionized water, and adjust the pH to 4 using an acetate buffer solution with a pH of 3.5 to obtain a cationic etherified starch solution. Mix the tannic acid / ε-polylysine solution and the cationic etherified starch solution, and gelatinize them on a magnetic stirrer at 95°C and 500rpm for 30min to obtain a uniform solution. The uniform solution was then cooled to 60°C and 0.6 g of AKD emulsion was added to obtain an antibacterial hydrophobic sizing solution (according to the different contents of ε-polylysine (ε-PL) in the sizing solution (0.1wt%, 0.3wt%, 0.5wt%), the sizing solutions were named TC / PL-0.1%, TC / PL-0.3%, TC / PL-0.5%).
[0066] 1.2.3 Impregnated bleached bamboo pulp paper
[0067] The bleached bamboo pulp base paper was immersed in a sizing solution at 60°C for 10 seconds, pressed at a pressure of 0.5 MPa for 10 minutes, and then dried in a flat dryer at 105°C for 15 minutes to obtain TC / PL coated paper (referred to as sizing paper); TC / PL coated papers prepared with different sizing solutions TC / PL-0.1%, TC / PL-0.3%, and TC / PL-0.5% were marked as TC / PL-0.1%, TC / PL-0.3%, and TC / PL-0.5% respectively.
[0068] 1.3 Characterization
[0069] 1.3.1 Scanning Electron Microscope (SEM)
[0070] The surface microstructure of the sized paper was analyzed using an Apreo S field emission scanning electron microscope (Thermo Scientific, Waltham, Massachusetts, America). Before testing, all samples were sprayed with gold.
[0071] 1.3.2 Fourier Transform Infrared Spectroscopy (FTIR)
[0072] The samples were analyzed using a Nicolet IS10 FTIR (Perkin Elmer Inc., Waltham, MA, USA) spectrometer at 4000–500 cm -1 Scan 32 times within the wavelength range with a resolution of 4cm -1 , the functional group changes of paper before and after sizing were tested.
[0073] 1.4 Performance
[0074] 1.4.1 Thickness and Basis Weight
[0075] All samples were kept in an environment of 23±1℃ and 55±2%RH before the test. The thickness of the paper was tested using a Schaubel thickness tester, and the thickness was measured at three different locations on the paper. The paper mass was measured using an analytical balance, and the quantitative value was calculated using formula (1):
[0076] g=m / A (1)
[0077] g is the sample weight (g / m 2 ), m is the sample mass (g), A is the sample area (m 2 )
[0078] 1.4.2 Mechanical properties
[0079] The paper was cut into strips of 15 mm × 180 mm and the tensile strength of the sample was measured under standard test conditions (23 ± 1 ° C and 50 ± 2% relative humidity) using a ZLD-300 electronic tensile testing machine (100 mm span). The breaking length and tensile index were calculated using formulas (2) and (3):
[0080] Lb=(S / 9.8g)×1000 (2)
[0081] Y=(S / g)×1000 (3)
[0082] Where Lb is the breaking length (km), S is the tensile strength (kN / m), g is the basis weight (g / m 2 ); Y is the tensile index (N·m / g)
[0083] 1.4.3 Whiteness and optical performance test
[0084] The whiteness of the sample was tested according to the Chinese national standard GB / T 7974-2002. The average value of three tests was taken for each mechanical property parameter, and the standard deviation was calculated.
[0085] The UV-visible spectra of the paper before and after sizing were measured in the wavelength range of 200-600nm using Cary100 UV-visible spectrophotometer.
[0086] 1.4.4 Antioxidant test
[0087] The antioxidant activity of the sample was obtained by scavenging DPPH free radicals. 50 mg of the sample was cut into small pieces (about 3.0×3.0 mm) and immersed in 8 mL of anhydrous ethanol and extracted at 60°C for 2 h. 3 mL of the sample extract and 3 mL of 0.1 mM DPPH solution were mixed evenly, reacted for 30 min under dark conditions, and the absorbance at 517 nm was measured using a UV-visible spectrometer. The DPPH free radical scavenging rate was calculated by formula (4):
[0088] DPPH (%)=[1-(AB) / C]×100% (4)
[0089] A = absorbance of DPPH + paper extract, B = absorbance of paper extract + 95% ethanol, C = absorbance of DPPH + 95% ethanol.
[0090] 1.4.5 Wettability
[0091] To explore the influence of TC / PL coated paper on the surface hydrophilicity, the contact angle (WCA) of water on the paper surface was measured at room temperature using an OCA20 contact angle tester (Dataphysics, Germany), and the volume of the test water was 5 μL. Each sample was tested at least three times, and the average value was calculated. To determine the wetting performance of TC / PL coated paper to acid and alkali solutions, acetic acid solution with a pH of 3.5 and sodium hydroxide solution with a pH of 12 were used to test the paper surface. Milk, Orange Juice, Coca-Cola and coffee were used as test solutions to test the wetting performance of common beverages on coated paper.
[0092] 1.4.6 Antimicrobial properties
[0093] The antibacterial properties of paper were tested according to the antibacterial ring test method in Section 5 of GB / T 42702-2023. Escherichia coli and Staphylococcus aureus were used as test bacteria.
[0094] 2. Results and Discussion
[0095] 2.1 Preparation and characterization of TC / PL coated paper
[0096] Cationic etherified starch and alkyl ketene dimer can enhance the fiber strength of paper and give it liquid-repellent properties. Adding tannic acid and ε-polylysine to the sizing solution can give the paper excellent antioxidant and antibacterial properties. TC / PL coated paper is obtained by impregnating bleached bamboo pulp base paper. The preparation process is as follows: Figure 1 shown.
[0097] Compared with bleached bamboo pulp paper, TC / PL coated paper has no obvious color change in appearance, only changing from the original white to light yellow. Figure 2 As shown in (a) Figure 2Uncoated refers to bleached bamboo pulp base paper). The thickness and basis weight of base paper and TC / PL coated paper are as follows: Figure 2 As shown in (b), the thickness and basis weight of TC / PL coated paper are approximately 110 μm and 43 g / m 2 , which increased by about 10% and 16.2% compared with the base paper. This is because the TC / PL sizing solution not only fills the pores inside the base paper fibers but also adheres to the fiber surface, causing an increase in thickness and basis weight. The increase in ε-PL content has little effect on paper thickness and basis weight, which means that it has little effect on the viscosity of the emulsion, so the amount of emulsion and fiber combination does not change much.
[0098] Figure 2 (c) is the FT-IR spectra of TC / PL coated paper and bleached bamboo pulp base paper. Compared with the base paper, the TC / PL coated paper has a -1 and 1192cm -1 The new absorption peak at 1236 cm-1 corresponds to the C=C and C=O stretching in the aromatic ring of TA. -1 The stretching vibration of CN appeared at 1641 cm -1 Move to 1611cm -1 , proving that TA and ε-PL interact with cellulose to produce hydrogen bonds. -1 The characteristic peak of β-ketoester bond appeared at the bottom of the paper, which indicated that the lyophobic groups of AKD and cellulose hydroxyl groups reacted to form covalent bonds during the drying process, thus enhancing the hydrophobicity of the paper.
[0099] 2.2TC / PL coated paper SEM
[0100] The surface morphology of base paper and TC / PL coated paper was characterized by scanning electron microscopy. Figure 3 As can be seen in (a), the surface of the base paper is composed of interwoven cellulose fibers, which form a network of micropores of varying sizes. After pulping, the bamboo pulp fibers show obvious fibrils, which can provide more hydrogen bonding sites and improve the bonding strength of the paper. Figure 3 (b)-(d) show TC / PL coated paper. Compared with the base paper, the pores of the base paper are obviously filled with TC / PL sizing liquid after impregnation, and the pores and microfibrils are significantly reduced with the increase of ε-PL. In addition, the TC / PL sizing liquid is also deposited on the surface of the paper fiber, which explains why the basis weight and thickness increase at the same time. The penetration of the emulsion into the paper blocks the pores inside the fiber, and the uniform and dense surface gives the coated paper good mechanical strength and barrier properties.
[0101] 2.3 Mechanical properties of TC / PL coated paper
[0102] Mechanical strength is an important indicator to measure the physical properties of paper, which directly affects its application in food packaging. Figure 4 As shown in (a), the tensile index of TC / PL coated paper is increased by about 25% compared with the base paper. When the ε-PL dosage is 0.1%, the tensile index of the coated paper can reach 58N·mg -1 , compared with 40N·mg of base paper -1 The tear length of coated paper has also been significantly improved, such as Figure 4 As shown in (b), this may be due to the enhancement of the inter-fiber bonding force. Tannic acid is a natural plasticizer that reduces the hardness of paper. The covalent bond between tannic acid and cellulose can increase the strength of cellulose, but tannic acid will reduce the hydrogen bonds between cellulose molecules, which generally causes a decrease in the tensile index and tear length of coated paper. Therefore, cationic starch is used as a dry strength agent for coated paper. Because it has a positive charge, it can tightly bind to the negatively charged fibers. The free glucose hydroxyl groups of starch can hydrogen bond with cellulose molecules, thereby improving the bonding strength between fibers. The use of cationic starch sizing can also improve the formation of paper sheets, reduce the uneven stress caused by fiber agglomeration, and provide a more uniform bonding of inter-fiber forces. In summary, TC / PL coating improves the mechanical properties of bamboo pulp base paper.
[0103] 2.4 Optical properties of TC / PL coated paper
[0104] The whiteness of paper directly affects the color rendering of printed products. Paper with high whiteness can reflect almost all color light, and the color of printed products will be bright and pure. Figure 4 As shown in (c), the brightness of bleached bamboo pulp base paper can reach 78%, and the brightness of TC / PL coated paper is about 69%. Compared with bleached bamboo pulp base paper, the brightness of TC / PL coated paper decreases less.
[0105] Tannin plays an important role in dyeing as a biological colorant in textiles, leather and other materials. Tannic acid is easily soluble in water, and its aqueous solution is light yellow. Its chromophore group is easy to combine with cellulose, so the bleached base paper appears light yellow after TC / PL impregnation, and the whiteness of the paper is slightly reduced. The phenolic hydroxyl group in tannic acid also has a strong absorption of ultraviolet rays. The UV-visible spectrum was used to test the shielding ability of TC / PL paper and bamboo pulp base paper against ultraviolet rays. The results are as follows: Figure 4As shown in (d). Within 200-280nm (UV-B and UV-C), TC / PL paper can block about 70% of ultraviolet rays. Within the range of 280-400nm (UV-A), coated paper can block about 50%-70% of ultraviolet rays, and with the increase of ε-PL content, the anti-ultraviolet performance of paper is gradually enhanced, which shows that ε-PL and TA have a synergistic effect in anti-ultraviolet. The synergistic anti-ultraviolet performance of tannic acid and ε-PL helps to prevent ultraviolet oxidation and thus extend the shelf life of food, which has great potential and advantages in food packaging.
[0106] 2.5 Antioxidant properties of TC / PL coated paper
[0107] The antioxidant properties of bleached base paper and TC / PL coated paper were evaluated by measuring their scavenging ability for DPPH. Figure 5 As shown in (a). The scavenging rates of base paper, TC / PL-0.1%, TC / PL-0.3% and TC / PL-0.5% for DPPH radicals were 0%, 95.8%, 96.5% and 95.8%, respectively. The change in ε-PL content did not significantly improve the antioxidant activity of coated paper. This is because the antioxidant activity of TC / PL coated paper is mainly contributed by TA. The DPPH radical scavenging model is mainly due to the delocalization of excess electrons on the DPPH molecule, which manifests as stable free radicals and produces a dark purple color. When the DPPH solution encounters an antioxidant that can provide hydrogen atoms, the hydrogen atoms of the antioxidant react with the DPPH radicals to terminate the chain reaction of free radicals, ultimately leading to the scavenging of the DPPH radicals and the fading and stabilization of the solution to light yellow. Tannic acid is a natural antioxidant that, due to its polyphenolic hydroxyl groups, can provide a large number of hydrogen atoms to capture free radicals and terminate oxidation reactions. Therefore, due to the presence of phenolic hydroxyl groups in TA, TC / PL coated paper can react with the DPPH solution to consume a large number of free radicals, causing the solution to fade from purple to yellow, as shown in Figure 5 As shown in (b), the high antioxidant property of TC / PL coated paper can delay food spoilage and can be used as a packaging material for food preservation.
[0108] 2.6 Liquid repellency of TC / PL coated paper
[0109] The hygroscopicity of paper is an important reason that limits its application in food packaging. The hydrophilicity of the base paper is significantly improved after being modified by TC / PL sizing liquid. Figure 6As shown in (b). Since cellulose fibers contain a large number of hydroxyl groups and are therefore hydrophilic, the water contact angle of bamboo pulp base paper is 0°, while the water contact angle of the modified TC / PL coated paper can reach over 135°. There are two main reasons for this: First, it is attributed to the presence of AKD. As a paper hydrophobic agent, AKD is widely used in the sizing of paper and paperboard. AKD itself has no charge and is difficult to adsorb onto the fiber through charge. Therefore, cationic starch is used as an emulsifier to give the AKD emulsion a positive charge opposite to the fiber charge, thereby increasing the retention rate of AKD on the fiber. At high temperature, AKD melts and spreads on the cellulose molecular chain. The hydrophobic groups of AKD can react with the hydroxyl groups of cellulose fibers to form β-ketoester bonds to produce a sizing effect, making the paper hydrophobic, such as Figure 6 (a). Secondly, the pores formed by the interweaving of cellulose fibers will facilitate the diffusion of water vapor, making the paper less water-resistant. Therefore, blocking the pores between fibers is also an effective way to improve the liquid resistance of paper. The TC / PL sizing solution not only reduces the gaps between fibers, but also makes the cellulose fibers and pores have excellent liquid repellency due to the liquid-repellent properties of AKD. This dual effect makes the coated paper have excellent water resistance. Figure 6 As shown in (c), TC / PL coated paper also exhibits excellent moisture resistance to some other common liquids (milk, orange juice, Coca-Cola and coffee), and these droplets all show a typical spherical structure on the coated paper. In addition, acetic acid droplets and sodium hydroxide droplets at pH = 3.5 and pH = 12 also maintain a non-wetting state on the coated paper, indicating that TC / PL coated paper is also acid and alkali resistant. The above studies show that the coated paper has great application potential in the fields of paper cups, beverage containers, etc.
[0110] 2.7 Antibacterial properties of TC / PL coated paper
[0111] The antibacterial activity of food packaging materials is of paramount importance in reducing microbial contamination and extending the shelf life of food. This study used the inhibition zone method to test the antibacterial properties of Escherichia coli and Staphylococcus aureus. The results are as follows Figure 7 As shown. Figure 7 As can be seen from (a) and (b), the TC / PL coated paper has a more significant inhibitory effect on Staphylococcus aureus. Even with a dosage of 1% ε-PL, it can still show an excellent inhibitory effect. The inhibitory effect on Escherichia coli increases significantly with the increase of ε-PL content. Figure 7As can be seen in (c), the base paper showed no inhibitory properties against the two test bacteria, while the diameter of the inhibition zone of Escherichia coli increased from 13.3mm to 14.2mm and then to 14.6mm as the ε-PL content of the coated paper increased from 0.1% to 0.3% and then to 0.5%, and the diameter of the inhibition zone of Staphylococcus aureus increased from 15.1mm to 15.0mm and then to 15.6mm. This is mainly because the surface of ε-PL has a large positive charge, which can bind to the cell membrane, DNA and some functional proteins, destroy the structure of the cell membrane and achieve an antibacterial effect. TA, as a natural polyphenol, has antibacterial, anti-inflammatory and antioxidant properties. It can bind to lipids on the cell membrane and certain enzymes in microorganisms to inhibit the activity of enzymes. Here, it synergizes with ε-PL to enhance the antibacterial properties of coated paper.
[0112] 3. Conclusion
[0113] On the basis of existing large-scale industrial production, the present invention successfully prepared a biomass cationic starch-based TC / PL coated paper with high antioxidant, antibacterial and hydrophobic properties through surface sizing. CS enhances the mechanical strength of bamboo pulp fiber, and the tensile index of the coated paper can reach 58N·mg -1 , which is 45% higher than the base paper. The reaction of AKD and cellulose to form β-ketoester greatly improves the hydrophilic properties of cellulose paper, and the water contact angle of TC / PL coated paper can reach more than 135°. In addition, it also has obvious non-wetting properties for milk, coffee, cola, orange juice, acidic and alkaline solutions. TA not only gives the coated paper strong antioxidant and UV shielding properties, but also cooperates with ε-polylysine to produce obvious antibacterial effects on Escherichia coli and Staphylococcus aureus. The renewability and biodegradability of cationic etherified starch and tannic acid from plant fibers and biomass raw materials make the prepared coated paper a green and environmentally friendly new food packaging material that can be applied to current industrial production and has broad application prospects.
[0114] Comparative Example 1
[0115] The bleached bamboo pulp base paper was immersed in a 30°C TC / PL-0.5% sizing solution for 10 seconds, pressed at a pressure of 0.5 MPa for 10 minutes, and then dried in a flat dryer at 105°C for 15 minutes to obtain TC / PL coated paper (that is, the only difference from the preparation of TC / PL-0.5% coated paper in Example 1 is that the temperature at which the base paper is immersed in the sizing solution is 30°C).
[0116] Results: The amount of sizing solution loaded on the coated paper prepared at this temperature was very small, and the weight of the paper increased by only 0.8 g / m before and after impregnation. 2 In addition, the tensile strength and breaking length of the coated paper also slightly decreased compared with those before immersion. Due to the low sizing liquid load, the coated paper did not show antibacterial effects on Escherichia coli and Staphylococcus aureus.
[0117] Comparative Example 2
[0118] The bleached bamboo pulp base paper was immersed in a 80°C TC / PL-0.5% sizing solution for 10 seconds, pressed at a pressure of 0.5 MPa for 10 minutes, and then dried in a flat dryer at 105°C for 15 minutes to obtain TC / PL coated paper (that is, the only difference from the preparation of TC / PL-0.5% coated paper in Example 1 is that the temperature at which the base paper is immersed in the sizing solution is 80°C).
[0119] Results: The coating of the coated paper prepared at this temperature has a uniform appearance, excellent mechanical properties, and shows obvious antibacterial effects on Escherichia coli and Staphylococcus aureus. However, the test found that the hydrophobicity of the coated paper decreased significantly, and the water contact angle was 103.8°. This is because AKD is hydrolyzed at high temperature to generate β-keto acid, which destroys the sizing effect of AKD.
[0120] Comparative Example 3
[0121] Weigh 9g of tannic acid (TA) and dissolve it in 100mL of deionized water to obtain a tannic acid solution. Weigh 0.8g of cationic etherified starch and dissolve it in 100mL of deionized water, and use an acetate buffer with a pH of pH=3.5 to adjust its pH to 4 to obtain a cationic etherified starch solution. After mixing the tannic acid solution and the cationic etherified starch solution, gelatinize them on a magnetic stirrer at 95°C and 500rpm for 30min to obtain a uniform solution. Then cool the uniform solution to 60°C, add 0.6g of AKD emulsion, and obtain sizing solution A.
[0122] The bleached bamboo pulp base paper was immersed in sizing solution A at 60°C for 10s, pressed at a pressure of 0.5MPa for 10min, and then dried in a flat plate dryer at 105°C for 15min to obtain coated paper A.
[0123] The same effect verification as in Example 1 was performed on coated paper A. The results showed that coated paper A exhibited similar hydrophobic, antioxidant, UV resistance and mechanical properties as in Example 1, but only exhibited a significant antibacterial effect on Staphylococcus aureus, and had no antibacterial effect on Escherichia coli.
[0124] Comparative Example 4
[0125] Weigh 9g of ε-polylysine and dissolve it in 100mL of deionized water to obtain an ε-polylysine solution. Weigh 0.8g of cationic etherified starch and dissolve it in 100mL of deionized water, and adjust its pH to 4 using an acetate buffer solution with a pH of 3.5 to obtain a cationic etherified starch solution. Mix the ε-polylysine solution and the cationic etherified starch solution and gelatinize them on a magnetic stirrer at 95°C and 500rpm for 30min to obtain a uniform solution. Then cool the uniform solution to 60°C, add 0.6g of AKD emulsion, and obtain sizing solution B.
[0126] The bleached bamboo pulp base paper was immersed in sizing solution B at 60°C for 10s, pressed at a pressure of 0.5MPa for 10min, and then dried in a flat plate dryer at 105°C for 15min to obtain coated paper B.
[0127] The same effect verification as in Example 1 was carried out on coated paper B. The results showed that the mechanical strength of coated paper B was slightly reduced, the hydrophobic properties were almost unchanged, but its antioxidant and UV resistance were greatly reduced, and it showed a weak antibacterial effect on Escherichia coli and Staphylococcus aureus.
[0128] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A sizing solution, characterized in that: The raw materials include tannic acid, ε-polylysine, cationic etherified starch, alkyl ketene dimer and water; The mass volume ratio of the tannic acid, ε-polylysine, cationic etherified starch, alkyl ketene dimer and water is (4-12) g: (0.2-1) g: (0.4-1.2) g: (0.6-1.5) g: 200 mL.
2. A method for preparing the sizing solution according to claim 1, characterized in that: The following steps are involved: Dissolve tannic acid in 1 / 2 volume of water, then add ε-polylysine to obtain a tannic acid / ε-polylysine solution; dissolving the cationic etherified starch in the remaining 1 / 2 volume of water to obtain a cationic etherified starch solution; The tannic acid / ε-polylysine solution is mixed with the cationic etherified starch solution and then gelatinized to obtain a uniform solution; Alkyl ketene dimer is added to the homogeneous solution to obtain the sizing solution.
3. The method for preparing the sizing solution according to claim 2, characterized in that: The pH of the cationic etherified starch solution is 4.
4. The method for preparing the sizing solution according to claim 2, characterized in that: The gelatinization is specifically performed at 95° C. and a rotation speed of 500 rpm for 30 minutes.
5. The method for preparing the sizing solution according to claim 2, characterized in that: The temperature at which the alkyl ketene dimer was added to the homogeneous solution was 60°C.
6. Use of the sizing solution as claimed in claim 1 in preparing coated paper.
7. A coated paper, characterized in that: The raw materials include base paper and the sizing solution described in claim 1.
8. A method for preparing coated paper according to claim 7, characterized in that: The following steps are involved: The base paper is immersed in the sizing solution, and then pressed and dried to obtain the coated paper.
9. The method for preparing coated paper according to claim 8, characterized in that: The immersion temperature is 60° C. and the time is 10 seconds; the pressing pressure is 0.5 MPa and the time is 10 minutes; the drying temperature is 105° C. and the time is 15 minutes.
10. Use of the coated paper according to claim 7 in preparing packaging materials.
Citation Information
Patent Citations
AKD sizing agent as well as preparation method and application thereof
CN112593450A
Preparation method of antibacterial environment-friendly straw paper
CN115182195A
Waterproof stain-resistant wallpaper and preparation method thereof
CN115821640A
Dry and wet strength improvement of paper products with cationic tannin
EP2239370A1